(untitled) - Marks, Eric A. (Hoboken, N.J., 2003)
Chapters include: Standards, Concepts, and Terminology; Web Services Adoption; Strategic Perspective of Web Services; Vertical Market Perspective of Web Services; Architecting for Competitive Advantage; Web Services Vendor Landscape.
Keywords: Công ty kinh doanh,Business enterprises,Information technology,Internet programming,World Wide Web; Mạng vi tính,Quản trị,Computer networks,Management,Management